Annual Optimal Performance Analysis of Micro Heat Pipe PV/T under Different Angles in Northwest China - Liu, Xiaomin; Wu, Qingbai; Li, Jinping; Novakovic, Vojislav (Journal of thermal science, 2025)
The exploitation of photovoltaic/thermal (PV/T) systems, which facilitate concurrent conversion of solar radiation into electrical and heat energies, presents substantial potential in the solar-abundant northwestern zone of China. This investigation endeavors to evaluate the efficacy of a micro heat pipe (M-HP) PV/T system via exhaustive experimental analysis conducted in Lanzhou. To improve the performance of M-HP-PV/T system, a comparison was made between the optimal angles for each day and the entire year. The system inside greenhouse exhibited an average photovoltaic conversion efficiency (PCE) and thermal conversion efficiency (TCE) of 12.32% and 42.81%. The system of external environment registered average PCE and TCE values of 12.99% and 21.08%. To further understand the system’s operational results, a mathematical model was constructed through the integration of experimental data, exhibiting good agreement between the simulated outcomes and empirical observations. The average solar irradiance of daily optimum angle was 728.3 W/m 2 ; the annual optimum angle was 29° with an average solar irradiance of 705.6 W/m 2 . The average annual total powers at the optimal angle outside the greenhouse and inside the greenhouse were 448.0 W and 398.7 W. The average annual total efficiencies at the optimal angle outside the greenhouse and inside the greenhouse were 40.8% and 56.9%. The total power in the greenhouse was lower by 49.3 W, while total efficiency in the greenhouse was higher by 16.1%.